PERAN AYAH DALAM PENDIDIKAN ANAK MENURUT AL-QUR’AN - Rahmatus Sa’idah (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2020)
Parents are a calling for people who have made us born into this world. They are father and mother. The person we interact with them every day. The figure of a mother as the first school for her children. And the father figure as a hero in his son's life. Then what is the view of the Qur'an about the roles of father and mother. Especially if you look at it now, all things that have to do with the child's life are the full responsibility of the mother. And as if the father only needs to be responsible for the financial life of the child in the form of food, shopping and children's clothing. There is even worse now, a father who no longer protects his child. So we need to see, how the demands of the Qur'an in terms of the role of the father towards his child. This paper contains the demands of the Qur'an for fathers in educating their children based on stories contained in the Al-Qur'an and other verses that indicate the meaning of the role of the father.